Improve Numerical Method for Solving Optimal Control Problems Using Predictor-Corrector Method - Y. Ajiya; A. Ishaku; A. U Kinafa; S. B Muhammad; B. P Chajire, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2023)
In this paper, the numerical solution of optimal control problems using predictor-corrector methods with a forward-backward sweep algorithm is presented. The algorithm is developed to solve the state variable forward in time and the adjoint system alongside the control functions backward in time. The starting values of the methods were obtained using the classical Runge-Kutta method. The proposed algorithm is implemented using MAPLE 18 software to avoid a computational error. Some numerical examples are presented to illustrate the accuracy, reliability, consistency, and effectiveness of the present method. Finally, the results obtained were compared with the exact solution, and it performed favorably.